Photometric distances to young stars in the inner Galactic disk : II. The region towards the open cluster Trumpler 27 at L = 355° - Perren, Gabriel Ignacio (2012)
Context. The spiral structure of the Milky Way inside the solar circle is still poorly known because of the high density of the material that causes strong extinction towards the Galactic center. Aims. We present results of the first extensive and deep color-color diagram (CCD) photometric survey carried out in the field of the open cluster Trumpler 27, an object immersed in a region of extremely high visual absorption in the constellation of Sagittarius not far from the Galaxy center. The survey covers almost a quarter of square degree. Methods. We look for young stars clumps that might plausibly be associated with spiral structure. Wide-field UBVI photometry combined with infrared information allows us to reconstruct the distribution in the reddening and distance of young stars in the field using the CCD and color-magnitude diagrams (CMD). Results. The analysis of our data, combined with extensive spectroscopy taken from the literature, shows that the real entity of Trumpler 27 as an open cluster is far from being firmly stated. In fact, instead of finding a relatively compact group of stars confined to a small distance range, we found that stars associated with Trumpler 27 are, indeed, a superposition of early-type stars seen along the line of sight extending over several kiloparsecs beyond even the center of the Galaxy. We demonstrate that at each distance range it becomes possible to generate a CMD resembling that of an open cluster. This way, our analysis indicates that what was considered an open cluster characterized by a significant age spread is a stellar continuum that reaches its maximum number of stars at approximately 3.5 kpc from the Sun, the distance of the Scutum-Crux arm approximately. After analyzing the way early-type stars distribute with distance, we found that some of these stellar groups may be linked, within the distance errors, with other inner spiral arms of our Galaxy, including the Near 3 kpc arm at approximately 5 kpc from the Sun. However, very young stars by themselves do not seem to trace strongly the inner spiral arms since they are distributed evenly across several kiloparsecs toward the center of the Galaxy. This is remarkably different to current HI and CO radio observation maps, which show inner spiral arms composed by discrete structures of gas with a well-defined inter-arm separation.